Radiogenic Heat Production in West Malaysian Granites and Implications for Geothermal Energy - Abdalmajed M. Shlof; Mohd H. Arifin; Muhammad T. Zakaria; Mohammad N. Akmal Anuar; Mahmoud M. Hassan (Lithosphere)
This study investigates the radiogenic heat production (RHP) in granitic rocks of West Malaysia, focusing on their association with hot springs and their implications for geothermal energy potential. Analysis of 139 granite samples from three major granite belts reveals significant variation in RHP, ranging from 1.5 to 17.83 μW/m³, with an average of 5.7 μW/m³ and 47% of values falling between 5 and 9 μW/m³. Notably, the West Belt exhibits higher RHP values compared to other regions, indicating its potential as a significant heat source. Granites associated with hot springs show a higher average RHP (6.65 μW/m³) than nonassociated granites (3.88 μW/m³). The study examines the relationships between RHP and various geochemical parameters, including U, Th, and K concentrations, SiO₂ content, and Th/U ratios. Findings suggest that RHP primarily contributes to the heat source of hot springs and geothermal systems in Peninsular Malaysia, particularly in the West Belt region. This research underscores the strong potential for geothermal energy development in West Malaysia, especially in areas with high RHP values and associated hot springs, and provides valuable insights for future geothermal exploration and development in the region.